2015
DOI: 10.3389/fpls.2015.00892
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Proton Gradient Regulation 5 (PGR5) and PGR5-Like 1 (PGRL1) proteins promote sustainable light-driven hydrogen production in Chlamydomonas reinhardtii due to increased PSII activity under sulfur deprivation

Abstract: Continuous hydrogen photo-production under sulfur deprivation was studied in the Chlamydomonas reinhardtii pgr5 pgrl1 double mutant and respective single mutants. Under medium light conditions, the pgr5 exhibited the highest performance and produced about eight times more hydrogen than the wild type, making pgr5 one of the most efficient hydrogen producer reported so far. The pgr5 pgrl1 double mutant showed an increased hydrogen burst at the beginning of sulfur deprivation under high light conditions, but in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 63 publications
5
54
1
Order By: Relevance
“…those strains with lower amounts of PGR5 evolved more H 2 (Figure S3). Together with the largely consistent results of decreased NPQ (Figure D) and the similar fold‐increase of H 2 production after 120 h of sulfur starvation (∼6‐fold based on volume, Table S2) in hpm91 and in another pgr5 mutant (Steinbeck et al ) derived from wild‐type strain 137c (Dent et al ), we conclude that disruption of PGR5 is the cause of the H 2 ‐overproducing phenotype in hpm91 . A pgrl1 mutant has also been reported to display enhanced H 2 ‐production phenotype (Tolleter et al ).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…those strains with lower amounts of PGR5 evolved more H 2 (Figure S3). Together with the largely consistent results of decreased NPQ (Figure D) and the similar fold‐increase of H 2 production after 120 h of sulfur starvation (∼6‐fold based on volume, Table S2) in hpm91 and in another pgr5 mutant (Steinbeck et al ) derived from wild‐type strain 137c (Dent et al ), we conclude that disruption of PGR5 is the cause of the H 2 ‐overproducing phenotype in hpm91 . A pgrl1 mutant has also been reported to display enhanced H 2 ‐production phenotype (Tolleter et al ).…”
supporting
confidence: 81%
“…These results indicate that hpm91 possesses a higher capacity of H2 production than the original pgr5 mutant, presumably due to their different genetic background. The latter strain, which was derived from a different wild‐type strain (137c, Dent et al ) but without the information on the flanking regions of the DNA rearrangement (Johnson et al ), was recently characterized by Steinbeck et al (). Nevertheless, NPQ (non‐photochemical quenching) was significantly decreased in hpm91 upon high light treatment (Figure D).…”
mentioning
confidence: 99%
“…Similarly, knocking out the genes coding for the proteins PGR5 and PGRL1, which mediate the back-donation of electrons from ferredoxin into the PQ pool during cyclic electron flow (Fig. 3f), caused a 10-fold increase in hydrogen production in Chlamydomonas (Steinbeck et al 2015). While protection of the hydrogenase due to higher oxygen consumption partly explained this increase, removal of a pathway that dissipates excess reducing power may also have forced the cell to channel excess reducing power to the hydrogenase as an alternative sink.…”
Section: How Can We Improve Coupling To Photosynthetic Electron Transmentioning
confidence: 99%
“…In this study, a higher residual PSII activity was seen for stm6 within the anaerobic phase and suggested as an explanation for the higher hydrogen production capacity, since both wild type and stm6 maintained electron flow to the hydrogenase by water-splitting and linear electron transport (Volgusheva et al, 2013). However, several studies demonstrated the competition between cyclic electron flow and hydrogen production in C. reinhardtii (Tolleter et al, 2011;Steinbeck et al, 2015), and the inability of stm6 to switch from linear to cyclic electron flow under anaerobic conditions (Kruse et al, 2005) should largely contribute to its elevated hydrogen production capacity.…”
mentioning
confidence: 72%